THE SHIFTING RELIGIOUS AUTHORITY OF THE INDONESIAN ULEMA COUNCIL (MUI) IN THE DYNAMICS OF ISLAMIC DIGITALIZATION IN INDONESIA - Prasetianti, Isnaeni Gelda; Kuswanjono, Arqam; Ali, Iqmi Qaisah; Afdhalia, Afifah Nabila; Faizah, Fatihatul (HUNAFA Jurnal Studia Islamika, 2025)
The development of digital technology has changed the pattern of religious knowledge consumption in Indonesia and triggered the fragmentation of authority that was previously institutionalized and centralized. Data from the Indonesian Internet Service Providers Association (APJII) shows that internet penetration has reached 221 million users or 79.5% of the population, confirming the digital space as the main arena for religious interaction. In this context, the Indonesian Ulema Council (MUI) as an official religious institution faces challenges in maintaining its legitimacy amid the rise of non-formal digital religious actors. This study aims to analyze the shift in religious authority in the digital society and evaluate the effectiveness of the MUI's official website (mui.or.id) as an authoritative channel. The method used is descriptive qualitative with the support of secondary quantitative data. The results show that the main preference of site users is for fatwa content (57.7%), followed by halal information (53.8%) and sharia economics (46.2%). The results of the analysis show that religious authority is now more decentralized and personalistic, challenged by the popularity of digital ustaz. Strengthening digital strategies, religious literacy, and cross-platform collaboration are key to maintaining the sustainability of the MUI's formal authority.